KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF METODE CONCEPT MAPPING - Juliasari, Rima; Zachriwan, Zachriwan (Universitas Muhammadiyah Bengkulu, 2016)
The new paradigm of learning has placed the students to participate actively in the learning process. One of the consequence is that the learning process must use the variative methods, not only about the transfer of knowledge from teacher to students. This research is more being focused on the objective of the research in action in the class to improve ability of mathematical understandingof students which performed in implement method by usingConcept Mapping. This research used classroom action research ini class VII B SMPN 15 Bengkulu city. This research was observation action in the class that done by callaborative between the researcher and teachers. In collecting the data used by some instrument suchs interview, observation sheet of teachers and students, and essay sheet of mathematical reasoning ability.Based on observation, the result of this research was, in learning by using learning method Concept Mapping was good. Activity of teachers and student show good category. The result of reasoning ability test in cyclewas ability of students show enought category (50% of 22 students) and in the next cycle improve become good category (100% of 22 students).Â Keywords: Concept Mapping, mathematical understanding